2011
DOI: 10.1053/j.ajkd.2010.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the Goal of the Fistula First Breakthrough Initiative for Prevalent Maintenance Hemodialysis Patients

Abstract: Background The Centers for Medicare & Medicaid Services (CMS) established a national goal of 66% arterio-venous fistula (AVF) use among prevalent hemodialysis (HD) patients for the current Fistula First Breakthrough Initiative (FFBI). The feasibility of achieving the goal has been debated. We examined contemporary patterns of AVF use among prevalent patients to assess the potential for attaining the goal by dialysis facilities and their associated end-stage renal disease (ESRD) Networks in the United States (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 16 publications
(14 reference statements)
1
51
0
Order By: Relevance
“…The early collaborative efforts of the nephrology community led to substantially higher prevalence rates of fistulas; however, this was accomplished with only modest success in decreasing catheter rates, suggesting that many AV grafts have been replaced with fistulas. 3 Recognizing not only the benefits of fistulas but also the risks associated with catheters, the Centers for Medicare & Medicaid Services (CMS) adjusted its breakthrough initiative, Fistula First, to elevate this "catheter last" concept as a coprimary goal. 4 In this issue of the AJKD, Pisoni et al 5 extend the findings of Lynch et al 3 (who reported on the early successes of Fistula First at increasing fistula rates) to evaluate trends for fistula and catheter prevalence, focusing on 2010 to 2013, a period during which CMS payment policy evolved to penalize facilities with lower fistula and higher catheter rates.…”
mentioning
confidence: 99%
“…The early collaborative efforts of the nephrology community led to substantially higher prevalence rates of fistulas; however, this was accomplished with only modest success in decreasing catheter rates, suggesting that many AV grafts have been replaced with fistulas. 3 Recognizing not only the benefits of fistulas but also the risks associated with catheters, the Centers for Medicare & Medicaid Services (CMS) adjusted its breakthrough initiative, Fistula First, to elevate this "catheter last" concept as a coprimary goal. 4 In this issue of the AJKD, Pisoni et al 5 extend the findings of Lynch et al 3 (who reported on the early successes of Fistula First at increasing fistula rates) to evaluate trends for fistula and catheter prevalence, focusing on 2010 to 2013, a period during which CMS payment policy evolved to penalize facilities with lower fistula and higher catheter rates.…”
mentioning
confidence: 99%
“…In this issue of the American Journal of Kidney Diseases , Lynch et al 2 provide a wealth of information regarding progress in achieving the AVF goals in the United States between 2007 and 2010. Overall, AVF use increased from 45.3% to 55.5% among the prevalent hemodialysis population.…”
mentioning
confidence: 99%
“…Lynch et al 2 highlight 2 important observations regarding vascular access management. First, the enormous variability in AVF use among dialysis networks, and within single networks, suggests major differences in practice patterns and is consistent with results from several prior publications.…”
mentioning
confidence: 99%
See 2 more Smart Citations